The scientific database of universidade federal do Paraná: From planning to implementation - de Lima, Karolayne Costa Rodrigues; Estevão, Janete Saldanha Bach; de Araújo, Paula Carina [UNESP]; Gonçalves, Lucas Henrique (My University, 2019)
The Scientific Database (BDC) of the Federal University of Paraná (UFPR) aims to make available the scientific data used from research that is published by the UFPR community in theses, dissertations, journal articles and other bibliographic materials. Information Science as it deals with the stages that make up the data management cycle belonging to the information management processes. In this sense, the challenge that BDC proposes is to be an institutional platform that will allow the researcher to manage the scientific research data collected and/or originated in scientific projects. The methodology of BDC implementation went through some steps such as: software selection, requirements selection, metadata pattern selection, content analysis of key international repository policies that served as the basis for the establishment of data deposition guidelines, specification of criteria for the creation of the plan data management, registration with the data repository indexer service, Re3data.org and dissemination to the academic community. As a result, it was observed the difficulty of researchers to disclose the data produced in the research processes, which shows the need to enable researchers to use the repository and still within the practices of open science. Finally, the understanding of the process of scientific production and the evolution of science in the context of e-Science are crucial to the success of data repositories as a service that is relevant to the needs of 21st century researchers.
La base de datos cientifica de la universidad federal do Paraná: Desde la planificación hasta la implementación
A base de dados científicos da universidade federal do Paraná: Do planejamento à implantação
Keywords: Data repository; Open data; Research data